Odkrivanje in osvajanje prostorov svobode v delih zgodnjih slovenskih literarnih ustvarjalk - Mihurko Poniž, Katja (Slavistična revija, 2013)
Early Slovene female authors discuss the category of space in their travelogues and problematize it in their narrative prose. The first text about foreign lands (Luiza Pesjak: "V Draždanih",1877) already presents the city as a space of freedom and a place where one can absorb art. Luiza Pesjak's attitude towards the beauty of natural, cultural, and historical sites is also revealed in her images of Italy. Female authors of the second generation who wrote at the end of the 19th century and in the beginning of the 20th century ventured into other European capitals as well as to the Orient (L. Poljanec: "Carigrajske vizije", Marica Gregorič: "Šumi Nil", etc.).
Keywords: 19.-20. st.; 19th-20th century; aleksandrinke; Gregorič Stepančič, Marica, 1876-1954; Kveder, Zofka, 1878-1926; Pajk, Pavlina, 1854-1901; Pesjak, Luiza, 1828-1898; Poljanec, Ljudmila, 1874-1948; potopisi; Slovene female writers; Slovene literature; slovenska književnost; slovenske pisateljice; Strnad Cizerlj, Marica, 1872-1954; travelogues